Different training programs of mini-basketball players have a different effect on physical and technical preparation - Matulaitis, K.; Rudzitis, A.; Barcaitis, M.; Kreivyte, R.; Butautas, R. (Baltic Journal of Sport and Health Sciences, 2020)
Background. Basketball coaches need to find or create an effective training program while developing and training mini-basketball players. Only an effective and certified training program can help optimize the training process and bring success. So our aim of the analysis was also to determine and evaluate the effectivity of different training programs for mini-basketball players (8-9 years old).